2018
DOI: 10.1002/jcp.27902
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression profile in monocytic myeloid‐derived suppressor cells at maternal–fetal interface in a mouse model of spontaneous abortion

Abstract: Background Monocytic myeloid‐derived suppressor cells (MO‐MDSCs) play an important role in maintaining normal pregnancy. However, it is still not clear what kind of changes in MO‐MDSCs may lead to miscarriage, and which gene expression changes take place when MO‐MDSCs migrate to the uterus as bone marrow‐derived cells. Methods We used flow sorting technology to obtain MO‐MDSCs from the maternal–fetal interface and bone marrow, respectively. Affymetrix 3′IVT expression profiling chip technology was used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Studies in human and mice report that a decreased percentage and activity of MDSCs in peripheral blood is associated with early miscarriage [9,29,33,34]. In microenvironment, MDSCs secret iNOS to catabolize L-Arg to citrullin and produce NO which downregulates the expression of the TCR ζ chain on T cells hence restrain T cells activity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in human and mice report that a decreased percentage and activity of MDSCs in peripheral blood is associated with early miscarriage [9,29,33,34]. In microenvironment, MDSCs secret iNOS to catabolize L-Arg to citrullin and produce NO which downregulates the expression of the TCR ζ chain on T cells hence restrain T cells activity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Köstlin and his group observed that healthy pregnant women have a signi cant accumulation of PMN-MDSCs in the blood during all stages of pregnancy [27]. Studies in human and mice report that a decreased percentage and activity of MDSCs in peripheral blood is associated with early miscarriage [9,29,33,34]. In microenvironment, MDSCs secret iNOS to catabolize L-Arg to citrullin and produce NO which downregulates the expression of the TCR ζ chain on T cells hence restrain T cells activity [14].…”
Section: Discussionmentioning
confidence: 99%